The Mechanisms of Inclusive Leadership on Newcomers’ Proactive Socialization Behaviors—An Exploration Based on the Proactive Motivation Model - Jingyi Shi; Long Ye; Junnan Ren (Behavioral Sciences)
This study advances newcomers’ socialization research by identifying and investigating the antecedents of newcomers’ proactive behaviors, a perspective often overlooked within the current studies, which primarily focuses on the outcomes of such behaviors. Based on the proactive motivation model, our core hypothesis is that inclusive leadership allows newcomers to experience psychological changes in control beliefs (can-do motivation), state promotion focus (reason-to motivation), and positive affect (energized-to motivation), which are stimulated following proactive behaviors. We further consider an individual values variable—individual power distance orientation—as the boundary condition on the influence of inclusive leadership. Research was conducted on 353 newcomers with less than one year of work experience to test the above hypothesis. The results show that inclusive leadership positively and indirectly influences the newcomers’ proactive behaviors via state promotion focus and positive affect. However, the mediating effect of control beliefs was not significant. Furthermore, the positive association between inclusive leadership and two kinds of newcomer proactive motivations, and their accompanying indirect impacts on newcomers’ proactive behaviors, was proved stronger at lower levels of individual power distance orientation. Additionally, it has been discovered in a follow-up complementary study that the effect of control beliefs on newcomers’ proactive behaviors is transmitted through positive affect.